Experimental and Theoretical Determination of Water-Jet Velocity for Disruptor Application Using High Speed Videography - Bhupesh Ambadas PARATE (Wojskowa Akademia Techniczna, 2019)
Experimental and theoretical determination of water-jet velocity using high speed videography for disruptor application is reported in this paper. Water-jet disruptor extensively uses the water as a liquid projectile. It helps to destroy improvised explosive devices (IEDs) or explosive devices (EDs) by breaking detonating cord in the system, making it non-operational. The use of such system against suspected objects is a fashion that continues to be met tremendous achievement. Such a device is also known as explosive ordnance disposal (EOD) disruptor. It is used by bomb technicians or squad to make disable and/or neutralize at a safe distance. The primary purpose of an EOD disruptor is to remotely open or provide destruction to suspected objects. To “remotely open” is to open the suspect objects, exposing their contents. “Provide destruction” means penetrating, cutting, or removing the components of the fusing system in order to make them disable. A secondary purpose of a disruptor is to create a means of access (for example, through a window or door of vehicle or into a trunk). Double and single base propellants are used in the experimental trials for assessing water-jet velocities. An attempt has been made to validate the water-jet velocity using experimentally high-speed videography for the first time and making its theoretical analysis by conducting the various trials at a laboratory with different propellants. The stand-off distance between disruptor and target is 0.5 m. This kind of research work is not reported in open access till the date. This is the newness of this research work. The experimental water-jet velocity for single base propellant varies from 349.63 to 503.56 m/s and for double base propellant it varies from 515.07 to 890 m/s. The theoretical water-jet velocity for single base and double base propellant works out to be as 616.44 m/s and 692.62 m/s respectively. From this research study, it is concluded that there is good agreement between theoretical and experimental results.
Keywords: Wodny układ miotający